2022
DOI: 10.3389/fphar.2022.879495
|View full text |Cite
|
Sign up to set email alerts
|

Review on Plant-Based Management in Combating Antimicrobial Resistance - Mechanistic Perspective

Abstract: Antimicrobial resistance (AMR) occurs when microbes no longer respond to any pharmacological agents, rendering the conventional antimicrobial agents ineffective. AMR has been classified as one of the top 10 life-threatening global health problems needed multilevel attention and global cooperation to attain the Sustainable Development Goals (SDGs) according to the World Health Organization (WHO), making the discovery of a new and effective antimicrobial agent a priority. The recommended treatments for drug-resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 178 publications
0
4
0
Order By: Relevance
“…Additionally, efforts are being made to investigate plant-based methods and natural products as potential solutions to antimicrobial resistance. It has been proposed that naturally occurring compounds (including plant metabolites), rather than fully synthetic molecules (such as sulfonamides, fluoroquinolones, and oxazolidinones) would be better suited to overcome AMR [ 151 , 152 ]. However, none of these strategies are in current widespread clinical use.…”
Section: Stewardship In Ophthalmologymentioning
confidence: 99%
“…Additionally, efforts are being made to investigate plant-based methods and natural products as potential solutions to antimicrobial resistance. It has been proposed that naturally occurring compounds (including plant metabolites), rather than fully synthetic molecules (such as sulfonamides, fluoroquinolones, and oxazolidinones) would be better suited to overcome AMR [ 151 , 152 ]. However, none of these strategies are in current widespread clinical use.…”
Section: Stewardship In Ophthalmologymentioning
confidence: 99%
“…Several plant-derived substances, including phenylpropanoids, terpenoids, betulinic and ursolic acids, and alkaloids, such as berberine, indole, and chelerythrine, exhibited anti-biofilm activity toward Pseudomonas aeruginosa, Klebsiella pneumoniae and staphylococcus biofilms. The disruption of intercellular communication, disturbance in cell-to-cell coaggregation, inhibition of cell mobility, inactivation of bacterial adhesins, or stimulation of bacterial dispersal are the suggested mechanisms of plants' secondary metabolites in inhibiting bacterial biofilm [106]. The screening of plant extracts and natural products for antimicrobial activity has revealed that medicinal plants are a potential source of novel anti-infective medicines [107].…”
Section: Pharmacological Activities Of Secondary Metabolitesmentioning
confidence: 99%
“…Given the rich and unique chemodiversity of plant‐derived compounds, their antimicrobial mechanisms may differ from conventional antimicrobial agents (Jubair et al., 2021; Porras et al., 2021). Thus, they will likely exert significant antimicrobial effects against pathogen microorganisms, including resistant strains, or augment the effect of antimicrobials against which the pathogens developed resistance (Arip et al., 2022; Huang et al., 2022). The prevailing notion is that natural compounds exert their antibacterial mechanism via chemical interference with the essential components’ synthesis/function and/or bypassing the conventional antibacterial resistance mechanisms (Khamenehn et al., 2019).…”
Section: Antimicrobial Mechanism Of Plant Byproduct Compoundsmentioning
confidence: 99%